(untitled) (Jurnal Wahana Konseling, 2024)
The aim of this research is to determine the effectiveness of folklore-based group guidance in developing students’ self-identity. This research uses quantitative experimental research methods with a one group pretest posttest research design. The research sample consisted of 9 students taken using purposive sampling technique. The research instrument used a Likert scale model, which was then analyzed using the normality test and the Wilcoxon test. In general, the research findings explain that folklore-based group guidance is effective in developing junior high school students’ self-identity. Specifically: 1) Students’ self-identity before being given folklore-based group guidance based on data processing results obtained an average score of 55.4 so that based on the pre-test results it can be seen that students’ level of self-identity tends to be moderate. 2). Students’ self-identity after being given folklore-based group guidance based on the results of data processing obtained an average score of 77.1 so that based on the post-test results it can be seen that the level of students’ self-identity tends to be high. It is hoped that the research results can contribute to subsequent research and provide an overview of the research series.